Luminal Lipid Regulates CD36 Levels and Downstream Signaling to Stimulate Chylomicron Synthesis - Tran, Thi Thu Trang (American Society for Biochemistry and Molecular Biology, 2011)
The membrane glycoprotein CD36 binds nanomolar concentrations of long chain fatty acids (LCFA) and is highly expressed on the luminal surface of enterocytes. CD36 deficiency reduces chylomicron production through unknown mechanisms. In this report, we provide novel insights into some of the underlying mechanisms. Our in vivo data demonstrate that CD36 gene deletion in mice does not affect LCFA uptake and subsequent esterification into triglycerides by the intestinal mucosa exposed to the micellar LCFA concentrations prevailing in the intestine. In rodents, the CD36 protein disappears early from the luminal side of intestinal villi during the postprandial period, but only when the diet contains lipids. This drop is significant 1 h after a lipid supply and associates with ubiquitination of CD36. Using CHO cells expressing CD36, it is shown that the digestion products LCFA and diglycerides trigger CD36 ubiquitination. In vivo treatment with the proteasome inhibitor MG132 prevents the lipid-mediated degradation of CD36. In vivo and ex vivo, CD36 is shown to be required for lipid activation of ERK1/2, which associates with an increase of the key chylomicron synthesis proteins, apolipoprotein B48 and microsomal triglyceride transfer protein. Therefore, intestinal CD36, possibly through ERK1/2-mediated signaling, is involved in the adaptation of enterocyte metabolism to the postprandial lipid challenge by promoting the production of large triglyceride-rich lipoproteins that are rapidly cleared in the blood. This suggests that CD36 may be a therapeutic target for reducing the postprandial hypertriglyceridemia and associated cardiovascular risks.